Cs promoted Ag/Al2O3 catalysts for selective catalytic reduction of NOx by methane: effect of SO2 and H2O - Rao, Komateedi N.; Ha, Heon Phil (ROYAL SOC CHEMISTRY, 2012)
Highly active alumina supported silver nano-particles were evaluated for SCR of NOx using methane in an excess oxygen atmosphere. Cs promoted Ag/Al2O3 catalysts showed high NO reduction activity. In addition, the prepared materials exhibited promotional effects in the presence of SO2 and H2O. The X-ray diffraction profiles of fresh and used catalysts indicated that the prepared materials are thermally stable up to 70 h of time-on-stream reaction. Activity results well correlated with the characterization data, which revealed that the high deNO(x) ability was due to superior NO adsorption properties as well as the presence of an appropriate amount of Ag+ and metallic Ag particles.
Keywords: ALUMINA CATALYSTS; AG; HYDROCARBONS; SCR